Race and politics : Asian Americans, Latinos, and whites in a Los Angeles suburb - Saito, Leland T., 1955- (University of Illinois Press, 1998)
By tracing grass-roots political organization along racial and ethnic lines, Race and Politics focuses on the construction of new identities, especially the panethnic affiliation "Asian American".
Keywords: Monterey Park (Calif.) -- Politics and government.; Monterey Park (Calif.) -- Race relations.; White people -- California -- Monterey Park.; Hispanic Americans -- California -- Monterey Park.; Asian Americans -- California -- Monterey Park.; Personnes blanches -- Californie -- Monterey Park.; Américains d'origine latino-américaine -- Californie -- Monterey Park.; Américains d'origine asiatique -- Californie -- Monterey Park.; Local.; American Government.; POLITICAL SCIENCE.; Emigration & Immigration.; Urban.; Sociology.; Asian American Studies.; Ethnic Studies.; California -- Monterey Park; White people; Race relations; Politics and government; Hispanic Americans; Asian Americans; Monterey Park, Calif.; Weisse.; Hispanos; Ethnische Beziehungen; Asiaten; Hispanos.; Asiaten.